Development of magic box learning media material circulatory system Class XI SMAN 16 Bulukumba - Astuti, Nuraevi; Taufiq, Ainul Uyuni; Rivai, Andi Tenri Ola (Journal of Islam and Science, 2023)
The goal of teaching strategies and instructional materials is to engage students in active, imaginative learning. This research aims to: 1) Create Magic Box learning materials for class XI circulatory system content at SMAN 16 Bulukumba by employing the ADDIE model; 2) Determine the level of validity of Magic Box learning materials for class XI circulatory system content at SMAN 16 Bulukumba; 3) Be aware of the practicality of Magic Box learning materials for class XI circulatory system content at SMAN 16 Bulukumba; and 4) Be aware of the level of validity of Magic Box learning materials for class XI circulatory system content. The ADDIE (analysis, design, development, implementation, and evaluation) development model is utilized in this type of research and development. Validity, practicality, and effectiveness were evaluated throughout the product development process. Twenty two (22) XI SMAN 16 Bulukumba students served as the subjects. The product's validity was assessed using a media validation sheet, the product's practicality was assessed using responses from students and educators, and the product's efficacy was assessed using a learning outcomes test. The validity level of the data was 3.8, which means it is very valid. The practicality level of the responses was 3.7, which means it is very practical. Students who took the Magic Box learning outcomes test scored 82%, which means it is very effective. According to the findings of the research, Magic Box learning materials should be used because they meet the requirements of being valid, useful, and effective.